The Global work of art world's fairs, biennials, and the aesthetics of experience - Jones, Caroline A. (University of Chicago Press, 2016)
Global biennials have proliferated in the contemporary art world, but artists'engagement with large-scale international exhibitions has a much longer history that has influenced the present in important ways. Going back to the earliest world's fairs in the nineteenth century, this book argues that “globalism” was incubated in a century of international art contests and today constitutes an important tactic for artists. As world's fairs brought millions of attendees into contact with foreign cultures, products, and processes, artworks became juxtaposed in a “theater of nations,” which challenged artists and critics to think outside their local academies. From Gustave Courbet's rebel pavilion near the official art exhibit at the 1855 French World's Fair to curator Beryl Madra's choice of London-based Cypriot Hussein Chalayan for the off-site Turkish pavilion at the 2006 Venice Biennale, artists have used these exhibitions to reflect on contemporary art, speak to their own governments back home, and challenge the wider geopolitical realm—changing art and art history along the way. Ultimately, Caroline A. Jones argues, the modern appetite for experience and event structures, which were cultivated around the art at these earlier expositions, have now come to constitute contemporary art itself, producing encounters that transform the public and force us to reflect critically on the global condition.